A Self-Adaptive Heuristic Algorithm for Combinatorial Optimization Problems - ALABAŞ USLU, ÇİĞDEM (ATLANTIS PRESS, 2014)
This paper introduces a new self-tuning mechanism to the local search heuristic for solving of combinatorial optimization problems. Parameter tuning of heuristics makes them difficult to apply, as parameter tuning itself is an optimization problem. For this purpose, a modified local search algorithm free from parameter tuning, called Self-Adaptive Local Search (SALS), is proposed for obtaining qualified solutions to combinatorial problems within reasonable amount of computer times. SALS is applied to several combinatorial optimization problems, namely, classical vehicle routing, permutation flow-shop scheduling, quadratic assignment, and topological design of networks. It is observed that self-adaptive structure of SALS provides implementation simplicity and flexibility to the considered combinatorial optimization problems. Detailed computational studies confirm the performance of SALS on the suit of test problems for each considered problem type especially in terms of solution quality.
Keywords: Metaheuristics; Combinatorial optimization; Parameter tuning; Adaptive parameter; VEHICLE-ROUTING PROBLEM; TABU SEARCH ALGORITHM; FLOW-SHOP PROBLEM; GENETIC ALGORITHM; SCATTER SEARCH; STRATEGIES; NETWORKS